2011
DOI: 10.1002/mabi.201100184
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Driven Gel Conveyer: Effect of Interactions Between Loaded Cargo and Self‐Oscillating Gel Surface

Abstract: A "self-oscillating" gel that swells and deswells periodically under constant conditions is developed as a novel biomimetic gel differing from conventional stimuli-responsive polymer gels. By utilizing the peristaltic motion of the self-oscillating gel, autonomous mass-transport systems can be realized. With the propagation of the chemical wave, the loaded gel cargo is autonomously transported by rotating on the surface. To apply the self-driven gel conveyer to a wider range of uses, it is important to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…It was suggested that the adhesion force between the cylindrical poly(AAm-co-MMA) gel and the self-oscillating gel sheet was too strong to apply the transport model because of their hydrophobic interaction. The adhesive force to prevent transportation is not significant for the other gels, which agrees with the prediction from swelling, zeta potential, and contact angle measurements [15].…”
Section: Design Of Autonomous Mass Transport Systemssupporting
confidence: 85%
See 2 more Smart Citations
“…It was suggested that the adhesion force between the cylindrical poly(AAm-co-MMA) gel and the self-oscillating gel sheet was too strong to apply the transport model because of their hydrophobic interaction. The adhesive force to prevent transportation is not significant for the other gels, which agrees with the prediction from swelling, zeta potential, and contact angle measurements [15].…”
Section: Design Of Autonomous Mass Transport Systemssupporting
confidence: 85%
“…11.3) [13][14][15][16]. It was found to be effective to copolymerize 2-acrylamido-2 -methylpropane sulfonic acid (AMPS) to a poly(NIPAAmco-Ru(bpy) 3 ) gel network to generate a large amplitude of volume change of the gel [13].…”
Section: Design Of Autonomous Mass Transport Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A model object, a cylindrical or spherical PAAm gel was put on the surface of self-oscillating gel sheet [18,[29][30][31]. It was observed that the object was transported on the gel surface with the propagation of the chemical wave as it rolled (Fig.…”
Section: Self-driven Gel Conveyer: Autonomous Transportation On the Smentioning
confidence: 99%
“…The influences of these surface properties on the transport behaviors were also investigated [30]. Instead of the homopolymer gel of PAAm, several kinds of copolymer gels consisting of AAm with AMPS, N-(3-aminopropyl)methacrylamide hydrochloride (APMA), N-(hydroxymethyl)acrylamide (HMAAm), and methyl methacrylate (MMA) were prepared as model cargos with different surface properties; positive or negative charge, more hydrophilicity or hydrophobicity, respectively.…”
Section: Self-driven Gel Conveyer: Autonomous Transportation On the Smentioning
confidence: 99%